Answer :

Given: n(A) = 54, n(B) = 39, n(B – A) = 13


Using the hint


n(B) = n(B – A) + n(A B)


39 = 13 + n(A B)


n(A B) = 39 – 13


n(A B) = 26


Visualizing the hint given,



We know that n(A B) = n(A) + n(B) – n(A B)


n(A B) = 54 + 39 – 26


n(A B) = 67


Hence n(A B) = 67


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Let A = {a, b, c,RS Aggarwal - Mathematics

If A and B be twoRS Aggarwal - Mathematics

(i) If A <span laRS Aggarwal - Mathematics

Using propeMathematics - Exemplar

If A and B are twRS Aggarwal - Mathematics

In a town of 10,0RS Aggarwal - Mathematics

If A and B are twRS Aggarwal - Mathematics

If <a name="MTBlaRS Aggarwal - Mathematics

If n(A) = 3 and nRS Aggarwal - Mathematics

For any sets A, BRS Aggarwal - Mathematics